Readmissions to Intensive Care: A Prospective Multicenter Study in Australia and New Zealand*. Issue 2 (February 2017) - Santamaria, John D.; Duke, Graeme J.; Pilcher, David V.; Cooper, D. James; Moran, John; Bellomo, Rinaldo
Abstract : Objectives: To determine factors independently associated with readmission to ICU and the independent association of readmission with subsequent mortality. Design: Prospective multicenter observational study. Setting: Forty ICUs in Australia and New Zealand. Patients: Consecutive adult patients discharged alive from ICU to hospital wards between September 2009 and February 2010. Interventions: Measurement of hospital mortality. Measurements and Main Results: We studied 10, 210 patients and 674 readmissions. The median age was 63 years (interquartile range, 49–74), and 6, 224 (61%) were male. The majority of readmissions were unplanned (84.1%) but only deemed preventable in a minority (8.9%) of cases. Time to first readmission was shorter for unplanned than planned readmission (3.2 vs 6.9 d; p < 0.001). Primary diagnosis changed between admission and readmission in the majority of patients (60.2%) irrespective of planned (58.2%) or unplanned (60.6%) status. Using recurrent event analysis incorporating patient frailty, we found no association between readmissions and hospital survival (hazard ratios: first readmission 0.88, second readmission 0.90, third readmission 0.44; p > 0.05). In contrast, age (hazard ratio, 1.03), a medical diagnosis (hazard ratio, 1.43), inotrope use (hazard ratio, 3.47), and treatment limitation order (hazard ratio, 17.8) were all independently associated with outcome. Conclusions: In this large prospective study, readmission to ICU was not an independent risk factor for mortality. Abstract : Supplemental Digital Content is available in the text.